2021
DOI: 10.21203/rs.3.rs-147865/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PNO1 regulates autophagy and apoptosis of hepatocellular carcinoma via the MAPK signaling pathway

Abstract: Background Some studies have reported that the activated ribosomes are positively associated with malignant tumors, especially in hepatocellular carcinoma (HCC). The RNA-binding protein PNO1, as a critical ribosome has been rarely reported in human tumors. Thus, the roles of PNO1 in HCC should be explored. Methods We collected 150 formalin-fixed and paraffin-embedded (FFPE) samples and 8 fresh samples to explore the expression and prognosis of PNO1 in HCC by immunohistochemistry, Western Blotting and RT-PCR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…3E). Taken together, the results suggested that PNO1 promote autophagy in HCC, consistence with our previous study [15]. To determine whether PNO1-mediated autophagy is related to ferroptotic cell death in HCC cancer cells, we used rapamycin or CQ co-treated with erastin to verify cell viability and cell death through CCK8 (Fig.…”
Section: Pno1 Is a Bona Fide Redox-responsive Repressor Of Ferroptosissupporting
confidence: 87%
See 2 more Smart Citations
“…3E). Taken together, the results suggested that PNO1 promote autophagy in HCC, consistence with our previous study [15]. To determine whether PNO1-mediated autophagy is related to ferroptotic cell death in HCC cancer cells, we used rapamycin or CQ co-treated with erastin to verify cell viability and cell death through CCK8 (Fig.…”
Section: Pno1 Is a Bona Fide Redox-responsive Repressor Of Ferroptosissupporting
confidence: 87%
“…Our previous study has shown that PNO1 is associated with the progression of various cancers, including HCC [15] and lung adenocarcinoma [16]. We further explored the molecular mechanism of PNO1 in regulating the malignant progression of HCC by performing differential protein enrichment analysis, which suggested that PNO1 was significantly associated with ferroptosis (Fig.…”
Section: Pno1 Is a Bona Fide Redox-responsive Repressor Of Ferroptosismentioning
confidence: 95%
See 1 more Smart Citation
“…Several proteins and drugs affect the progression and metastasis of liver cancer via this pathway. For example, PNO1 mediated the autophagy and apoptosis of liver cancer via this pathway [20]. EB2 also promoted liver cancer proliferation and metastasis via MAPK pathway by regulating microtubule dynamics [21].…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein were loaded on gels and separated by SDS‐PAGE. Then, proteins were transferred to PVDF membranes (Immobilon‐P; Millipore) and blocked with 5% milk or bovine serum albumin, followed by incubation with primary and secondary antibodies 23 . Primary antibodies were METTLE14 (1:2000, CST, 51104), CSF1R (1:1000, abcam, ab229188), and GAPDH (1:10000, abcam, ab181602) antibodies.…”
Section: Methodsmentioning
confidence: 99%